APPLYING INDUCTIVE METHOD TO IMPROVE THE ABILITY IN USING SUFFIX-ING OF GRADE XI STUDENTS AT MAN 1 PALU - Al-Muthmainnah, Al-Muthmainnah (Fakultas tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Palu, 2016)
This research aims at describing the inductive method in using suffix -ing. The population of study is the students of grade XI of MAN 1 PALU, in which the experimental and control group consist of 25 students for each. The method used in this study is quasi-experimental research design-nonequivalent control group design. It is done in eight meetings. The variables of this research are inductive method and ability in using suffix -ing. The samples of this research are students of grade XI IPS 2 and IPS 3, selected through purposive sampling technique. Based on the results of the study, it is proved that applying inductive method has overcome the students’ problem. It has affected students’ attention, understanding, and achievement. It is found that first, there are 18 students (72%) who are motivated to learn English. Then, T-counted 6.5 is higher than T-table (2.012). It means that Ho is rejected and Hα is accepted. Finally, applying inductive method affects the ability in using suffix –ing of grade XI students at MAN 1 PALU.